Lie Group Classification of a Generalized Lane-Emden Type System in Two Dimensions - Motlatsi Molati; Chaudry Masood Khalique (Journal of Applied Mathematics)
The aim of this work is to perform a complete Lie symmetry classification of a generalized Lane-Emden type system in two dimensions which models many physical phenomena in biological and physical sciences. The classical approach of group classification is employed for classification. We show that several cases arise in classifying the arbitrary parameters, the forms of which include amongst others the power law nonlinearity, and exponential and quadratic forms.